BS EN 63044-5-2 AMD1. Home and Building Electronic Systems (HBES) and Building Automation and Control Systems (BACS). Part 5-2. EMC requirements for HBES/BACS used in residential, commercial and light-industrial environments (25th October 2019) - British Standards Institution,
No abstract available